Neuroprotective Potential and Underlying Pharmacological Mechanism of Carvacrol for Alzheimer’s and Parkinson’s Diseases - Javed, Hayate; Mohamed Fizur, Nagoor Meeran; Kumar Jha, Niraj; Md. Ashraf, Ghulam; Ojha, Shreesh (Current Neuropharmacology, 2023)
The phytochemicals have antioxidant properties to counter the deleterious effects of oxidative stress in the central nervous system and can be a promising drug candidate for neurodegenerative diseases. Among various phytochemicals, constituents of spice origin have recently received special attention for neurodegenerative diseases owing to their health benefits, therapeutic potential, edible nature, and dietary accessibility and availability. Carvacrol, a phenolic monoterpenoid, has garnered attention in treating and managing various human diseases. It possesses diverse pharmacological effects, including antioxidant, anti-inflammatory, antimicrobial and anticancer. Alzheimer's disease (AD) and Parkinson's disease (PD) are major public health concerns that place a significant financial burden on healthcare systems worldwide. The global burden of these diseases is expected to increase in the next few decades owing to increasing life expectancies. Currently, there is no cure for neurodegenerative diseases, such as AD and PD, and the available drugs only give symptomatic relief. For a long time, oxidative stress has been recognized as a primary contributor to neurodegeneration. Carvacrol enhances memory and cognition by modulating the effects of oxidative stress, inflammation, and Aβ25-35- induced neurotoxicity in AD. Moreover, it also reduces the production of reactive oxygen species and proinflammatory cytokine levels in PD, which further prevents the loss of dopaminergic neurons in the substantia nigra and improves motor functions. This review highlights carvacrol's potential antioxidant and anti-inflammatory properties in managing and treating AD and PD.
Keywords: Parkinson’s disease